'Critical Pathways' – Training and Investigating the Art of Choreography-Making with Rosemary Butcher. Issue 2 (22nd March 2021) - Sachsenmaier, Stefanie Gabriele
Abstract : This article discusses the pedagogic practice of British choreographer Rosemary Butcher (1947–2016) with a particular focus on the ways she mentored dancers and choreographers as part of her self-curated workshop series Critical Pathways, programmed over a number of years at Independent Dance in London. Drawing on archive materials, personal research notes as well as practitioner interviews, the article draws out some of the idiosyncratic pathways of dance training that practitioners encountered as part of the series, and the ways these continue to influence their ongoing practice. The writing thematises Butcher's signature use of language and conceptual tools for choreography-making, as well as her approach to teaching and mentoring dance practitioners, which was inextricably tied to her choreographic practice. Never seeming to settle on a formula that had worked before, there was an arguably timeless and endlessly adaptable inexhaustibility and curiosity to her approach to making that are key qualities of inventive practice. The article further discusses the ways that Butcher instigated processes of critical self-reflection and approaches to reinvention as part of a continual investigation into what dance and choreography might be.